Sosialisasi Kemampuan Motorik Dasar Pasca Pembelajaran Daring Pada Siswa Sekolah Dasar - Purwoto, Septyaningrum Putri; Himawan, Agus; Handayani, Heni Yuli; Anwar, Khoirul; Widodo, Haryo Mukti; Utama, Fajar Hamdhan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The COVID-19 pandemic situation has changed the face-to-face learning model to online learning. This certainly presents its own challenges for practical subject teachers such as PJOK teachers. In the direct learning process, PJOK learning is related to motor skills from sports game models accompanied by habituation of healthy lifestyles. With the change in learning models in a pandemic situation, the learning process, especially in PJOK subjects at the elementary school level, has also undergone adjustments. This service aims to provide socialization of basic motor skills after online learning at SDN Kemayoran 3 Bangkalan. The participants of this socialization were upper grade elementary school students (Grades 4, 5, and 6) a total of 21 male and female students at SDN Kemayoran 3 Bangkalan. Community service activities are carried out through several stages of activities, including: Preparation and Briefing, Implementation, and Program Sustainability Planning. This dedication to basic motor skills after online learning at SDN Kemayoran 3 Bangkalan was successful. This is because, after the socialization, students understand more about basic motor skills for elementary school students. In addition, students understand that the impact of online learning during the COVID-19 pandemic affects basic motor skills, so with this socialization students can know their basic motor skills and get knowledge and suggestions so they can improve their basic motor skills.